UPAYA-UPAYA MARKETING STRATEGI DALAM MENINGKATKAN JUMLAH MAHASISWA DI FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN PGRI PALEMBANG - Kurniati, Kurniati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The journal tells of the Faculty of Mathematics, University of PGRI Palembang in finding prospective students. State University of PGRI Palembang consist of two (2) courses are Physics and Biology. The efforts made in marketing -upaya among others Promotion of service of a good, personal selling, publicity and word of mouth, the arena of creativity in Pedestrian road Sudirman. And barriers are inadequate campaign funds Keywords— marketing strategy, Increasing Number students